2021
DOI: 10.1038/s41598-021-86317-9
|View full text |Cite|
|
Sign up to set email alerts
|

The relative deficit of GDF15 in adolescent girls with PCOS can be changed into an abundance that reduces liver fat

Abstract: A prime concern of young patients with Polycystic Ovary Syndrome (PCOS) is the control of body adiposity, given their tendency to gain weight and/or their difficulty to lose weight. Circulating growth-and-differentiation factor-15 (GDF15) facilitates the control of body weight via receptors in the brainstem. C-reactive protein (CRP) and insulin are endogenous GDF15 secretagogues. We hypothesised that PCOS in non-obese adolescents is characterised by low concentrations of circulating GDF15, when judged by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“… 7 8 The new treatment was a low-dose combination of three generics (SPIOMET), 6 namely spironolactone 50 mg/day (to activate brown adipose tissue), 9 pioglitazone 7.5 mg/day (to double high-molecular-weight adiponectinaemia, 10 and to prioritise subcutaneous adipogenesis) 11 and metformin 850 mg/day (to triple the circulating concentrations of appetite-attenuating GDF15). 12 SPIOMET does not elicit a loss of body weight, but redistributes body fat from ectopic to subcutaneous depots, thereby conferring more broadly normalising benefits than OC, in particular on liver fat (by MRI) and on post-treatment androgen excess and ovulation rate 6 13 ( online supplemental table 1 ). 10.1136/bmjgast-2020-000574.supp1 …”
mentioning
confidence: 99%
“… 7 8 The new treatment was a low-dose combination of three generics (SPIOMET), 6 namely spironolactone 50 mg/day (to activate brown adipose tissue), 9 pioglitazone 7.5 mg/day (to double high-molecular-weight adiponectinaemia, 10 and to prioritise subcutaneous adipogenesis) 11 and metformin 850 mg/day (to triple the circulating concentrations of appetite-attenuating GDF15). 12 SPIOMET does not elicit a loss of body weight, but redistributes body fat from ectopic to subcutaneous depots, thereby conferring more broadly normalising benefits than OC, in particular on liver fat (by MRI) and on post-treatment androgen excess and ovulation rate 6 13 ( online supplemental table 1 ). 10.1136/bmjgast-2020-000574.supp1 …”
mentioning
confidence: 99%
“…Metformin has pleiotropic effects but is generally considered to serve as a net "insulin sensitiser" in conditions of ectopic adiposity with insulin resistance; in addition, it raises AMPK activity, and the circulating concentrations of Growth-and-Differentiation Factor 15 (GDF15), a peptide hormone that reduces hepatic steatosis and raises intestinal glucose utilization thereby promoting weight loss [59][60][61]. Metformin was first approved in 1959, and since then several FDCs have been approved for the treatment of type 2 diabetes as first-and/or second-line therapies [62].…”
Section: Reduction Of Ectopic Fat In "Mismatch" Girls With Accelerate...mentioning
confidence: 99%
“…One study (reported in five articles/sub-studies) 46 , 47 , 48 , 49 , 50 with moderate RoB compared low-dose anti-androgens (spironolactone 50 mg daily) + metformin + pioglitazone (SPIOMET) against COCP for 12 months in adolescent girls with PCOS (n = 62 in the main study). The SPIOMET group had reduced hirsutism (WMD [95% CI]: −3.00 [−5.77, −0.23], p = 0.03), SHBG (−29.00 nmol/l [−39.56, −18.44], p < 0.0001), fasting insulin (−62.00 pmol/l [−81.40, −42.60], p < 0.0001), ALT (−0.09 μkat/l [−0.16, −0.02], HOMA-IR (−1.80 [−2.42, −1.18], p < 0.0001), LDL (−0.05 mmol/l [−0.78, −0.22] p = 0.0004), CRP (−18.10 mmol/l [−25.75, −10.45], p < 0.0001), and FAI (−2.20 [−4.38, −0.02], p = 0.05), but higher androstenedione (1.00 nmol/l [0.29, 1.71], p = 0.006) compared with the COCP group.…”
Section: Resultsmentioning
confidence: 99%